Unconventional Sisterhood Feminist Catholic Nuns in the Philippines - Claussen, Heather (University of Michigan Press, 2001)
Unconventional Sisterhood is an ethnographic exploration of the ways in which Filipina Missionary Benedictine Sisters are renegotiating traditional understandings of gender, religious responsibility, and national identity in the context of a rapidly globalizing nation. Unlike the popular stereotypes of staid sisters cloaked in rigid religious dogmatism, they are doing so by telling jokes, engaging in eclectic religious rituals, maintaining connections with a local nationalist cult, and committing themselves to a radical and feminist politics. This work represents an important addition to scholarship on Philippine feminism. It is one of few ethnographies that focuses on female monasticism-of particular cultural importance in the Christian Philippines, where nuns enjoy relatively high social status and freedom from many of the traditional constraints delineating Filipina lives. It is noteworthy as well for its focus on metropolitan Manila-a socially complex, dynamic, diverse, and understudied environment.